1. Rút gọn các biểu thức sau: a. A = 1002 – 992+ 982 – 972 + … + 22 – 12 b. B = 3(22 + 1) (24 + 1) … (264 + 1) + 12 c. C = (a + b + c)2 + (a + b –

Question

1. Rút gọn các biểu thức sau:
a. A = 1002 – 992+ 982 – 972 + … + 22 – 12
b. B = 3(22 + 1) (24 + 1) … (264 + 1) + 12
c. C = (a + b + c)2 + (a + b – c)2 – 2(a + b)2
2. Chứng minh rằng:
a. a3 + b3 = (a + b)3 – 3ab (a + b)
b. a3 + b3 + c3 – 3abc = (a + b + c) (a2 + b2 c2 – ab – bc – ca)

in progress 0
Cora 1 tuần 2021-09-05T18:09:12+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-05T18:10:46+00:00

    Đề vậy mới đúng nè bạn :))?

    $\text{Bài 1: Rút gọn các biểu thức sau:}$

    `a, A = 100^2 – 99^2+ 98^2 – 97^2 + … + 2^2 – 1^2`

    `=(100-99)(100+99)+(98-97)(98+97)+…+(2-1)(2+1)`

    `=(1+100).100:2`

    `=5050`

    `b, B = 3(2^2 + 1) (2^4 + 1) … (2^{64} + 1) + 1^2`

    `=(2^2-1)(2^2+1)(2^4+1)(2^8+1)….(2^{64}+1)+1`

    `=(2^{16}-1)(2^{16}+1)(2^{32}+1)….(2^{64}+1)+1`

    `=2^{128}-1+1=2^{128}`

    ` c, C = (a + b + c)^2 + (a + b – c)^2 – 2(a + b)^2`

    `=a^2+b^2+c^2+2ab+2ac+2bc+a^2+b^2+c^2+2ab-2ac-2bc-2(a^2+2ab+b^2)`

    `=2c^2+0+0+0`

     `=2c^2`

     

    0
    2021-09-05T18:10:53+00:00

    Giải thích các bước giải:

    1.a)A = 1002 – 992+ 982 – 972 + … + 22 – 12

    ⇔A=(1002 – 992)+ (982 – 972) + … + (22 – 12)

          =10+10+…+10 (có 50 số 10)

          =50.10=500

    c) C = (a + b + c)2 + (a + b – c)2 – 2(a + b)2

           = (a+b)²+c²+2.c.(a+b)+(a+b)²+c²-2.c.(a+b)-2.(a+b)²

           =2c²

    2)a) Xét VP=(a + b)3 – 3ab (a + b)

    =a³+3a².b+3.ab²+b³-3a².b-3ab²

    =a³+b³

    ⇒đpcm

    b)Xét VP=(a + b + c) (a2 + b2+ c2 – ab – bc – ca)

    =a³+a.b²+ a.c² -a²b-abc-ca²+ba²+b³+bc²-ab²-cb²-abc+c³+ca²+cb²-abc-bc²-ac²

    =a³+b³+c³-3abc

    ⇒đpcm

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )